Covid-19: Effect on Hemostasis - Dmitrii V, Zabolotsky; Viktor A, Koryachkin; Viktor.G, Puzyrev (Asian Pacific Journal of Environment and Cancer, 2020)
Since December 2019, the first cases of coronavirus infection began to be registered, by now there is enough data accumulated to analyze the pathogenesis of the disease, as well as to develop etiopathogenetic treatment. The cytokine storm and coronaviral induced coagulopathy are considered to be the main pathogenesis link, which made possible to develop an etiopathogenic treatment. Cytokine Storm destroys precursor cells and reduces platelet production. The further formation of autoimmune complexes leads to thrombocytic destruction and induces damage to the endothelial cells of lung capillaries. Recommended direct parenteral anticoagulants treatment with low-molecular weight heparin forms (LMHs).